VP198 Efficient Retrieval Of Trial Protocols: An Empirical Study. (2017) - Sutton, Anthea; de la Cruz, Maria del Carmen Galvan; Booth, Andrew; Leaviss, Joanna
Abstract : INTRODUCTION: Registration of trial protocols has become increasingly important in recent years. In the context of systematic reviews, published trial protocols facilitate the identification of studies. Data recorded in trials registers requires standardization to assist with ease of identification, and availability of the most current protocol version. Searching sources of trial protocols, for example trials registers, has issues relating to currency, coverage, functionality and indexing. An empirical study was conducted in the context of a funded systematic review, to establish; the proportion of trial protocols retrievable, the most effective retrieval methods, barriers to retrieving protocols, and whether the most easily retrieved protocol copy remains the document of record. METHODS: In a systematic review of primary care interventions for medically unexplained symptoms, seventy-four trials were identified as potential included studies. To search for the seventy-four trial protocols, multiple sources and methods were utilized to identify the the differential coverage of sources and the relative efficiency of retrieval methods. Retrieval methods included searching trials registers and bibliographic databases, internet searching, checking journal websites and contacting authors. RESULTS: Results included; (i) number of trial protocols that were referenced in the corresponding study publication(s), (ii) percentage of protocols indexed in each checked source, including MEDLINE and various trials registers, (iii) number of authors that responded to email contact, (iv) number of authors that provided a reference to, or copy of, the protocol. Information on when the trial protocol was published, funding sources, and trial registration, was also recorded. CONCLUSIONS: Conclusions are made regarding the coverage of different sources of trial protocols. This will enable Information Specialists to prioritize retrieval methods for identifying trial protocols to inform future search methods guidance. The main barriers to retrieving protocols are discussed together with recommendations for future empirical studies.